2019
DOI: 10.3390/nu11010100
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexic Tendency in Polish Students: Exploring Association with Dietary Patterns, Body Satisfaction and Weight

Abstract: Body dissatisfaction is central to clinically diagnosed eating disorders (ED) and seems to be important in causing other non-clinical disorders, including orthorexia nervosa (ON). It can also affect eating behaviors. The aim of this study was to assess the associations of ON tendency with dietary patterns (DPs) and body satisfaction. The data were collected in 2017 through questionnaire survey among 1120 students of health-oriented and other academic programs from seven universities in Poland. Principal compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 87 publications
(120 reference statements)
4
21
1
7
Order By: Relevance
“…It can be assumed that due to the contrasting eating habits of people showing only ON tendency ("ON and without ED") and only ED symptoms ("ED and without ON"), no differences were found in the eating habits of people within the group "ON and ED." In addition, these people were characterized by less frequent consumption of sugar-rich and refined products, which was confirmed by the results of the previous studies on ON [10,26,27] and both AN subtypes-restrictive and binge eating or purging [58,59]. At the same time, people who showed both ON tendency and ED symptoms ("ON and AN") often consumed meat and meat products (upper tertile of DP).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…It can be assumed that due to the contrasting eating habits of people showing only ON tendency ("ON and without ED") and only ED symptoms ("ED and without ON"), no differences were found in the eating habits of people within the group "ON and ED." In addition, these people were characterized by less frequent consumption of sugar-rich and refined products, which was confirmed by the results of the previous studies on ON [10,26,27] and both AN subtypes-restrictive and binge eating or purging [58,59]. At the same time, people who showed both ON tendency and ED symptoms ("ON and AN") often consumed meat and meat products (upper tertile of DP).…”
Section: Discussionsupporting
confidence: 78%
“…However, ON does not include the primary symptoms of AN or BN, such as the fear of being obese, an excessive preoccupation with one's body, and a distorted perception of body image [9]. Moreover, a previous study reported that individuals with ON tendency expressed greater satisfaction with their upper body [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utility of the ORTO-15 that was used in presented study has been widely discussed, and some authors claim that this tool measures only healthy eating, and not pathologically healthful eating [19,44]. However, despite many flaws, the ORTO-15 is still the most commonly used psychometric tool [45][46][47][48][49]. There are a few diagnostic tools that are used to assess orthorexia nervosa in general population (ex.…”
Section: Discussionmentioning
confidence: 99%
“…It is an eating disorder that might be hazardous to the health and life of the individual concerned, because it can lead to malnutrition, metabolic acidosis, severe nutrients deficiencies or other health disorders in the human body [1]. To assess the risk of orthorexia in an individual, the ORTO-15 questionnaire based on the BOT (Bratman Orthorexia Test) is typically used [2]. This disorder can affect people with features such as perfectionism, obsessive compulsive diet, or other eating disorders in the patient's history.…”
mentioning
confidence: 99%